Model Hub Median Problem Dengan Batasan Travel Time - Ibrahim, Faisal; Rusdiansyah, Ahmad (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
This article describes the development of an uncapacitated p-hub median problem model. The established model will be applied in determining the location of the hub. Generally in the median p-hub model problem, it is known that the number of hubs built with the total cost minimization function. In this developed model, there is no limit to the number of hubs and the function of the intended destination is how many hubs are built. The model also looks for where the hub location will be built and which nodes are allocated to each hub. By eliminating the limitation of the number of hubs built, the model adds a total total timeout limit. The numerical experiments are dealing with the model. The solution to solve the model using excel solver. So that it will be designed spread sheet excel appropriate model. In numerical experiments, dummy data representing real systems will be used with the aim of shortening computational time. Numerical experiments are performed in several conditions scenarios. Computational results generate the location of hubs and nodes allocated to each hub with various experimental scenarios.